Distribution modeling for Colorado SWAP plants of greatest conservation need: interim report - April 2022 - Decker, K., author; Smith, J. P., author; Handwerk, J., author; Doyle, G., author; Panjabi, S., author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2022)
The revised 2015 Colorado State Wildlife Action Plan (SWAP) includes 117 Plant Species of Greatest Conservation Need (PGCN) in the Rare Plant Addendum (Colorado Parks and Wildlife 2015). These species are ranked globally critically imperiled (G1) or imperiled (G2), at risk throughout their range and under threat of extinction. Known locations of these species are recorded in a statewide geospatial database maintained by the Colorado Natural Heritage Program (CNHP). However, surveys for these species have not been comprehensive, and therefore information on their distribution is incomplete. For this project, models of species distribution were created using information on known locations and species habitat requirements. These distribution models will be included in the conservation data sharing platform, the Colorado Conservation Data Explorer (CODEX), in order to help conserve and protect these PGCN though environmental review and conservation planning.
Keywords: imperiled species; extinction; Colorado; conservation; protection